Randomized Controlled Trials of Blood Pressure Lowering in Hypertension - Alberto Zanchetti; Costas Thomopoulos; Gianfranco Parati (2015)
Sixty-eight blood pressure (BP)–lowering randomized controlled trials (defined as randomized controlled trials comparing active treatment with placebo, or less active treatment, achieving a BP difference, performed between 1966 and end 2013 in cohorts with ≥40% hypertensive patients, and exclusive of trials in acute myocardial infarction, heart failure, acute stroke, and dialysis) were identified and meta-analyzed grouping the randomized controlled trials on the basis of clinically relevant questions: (1) does BP lowering reduce all types of cardiovascular outcome? (2) Is prevention of all outcomes proportional to the extent of systolic, diastolic, and pulse BP? (3) Have all classes of BP-lowering drugs been shown capable of reducing all types of cardiovascular outcome? (4) Is BP lowering beneficial when intervention is initiated at any grade (or stage) of hypertension? (5) Do BP-lowering randomized controlled trials provide evidence about systolic BP and diastolic BP targets of treatment? (6) Should BP-lowering treatment be preferentially addressed to patients in higher risk categories promising larger absolute treatment benefits? The results of these meta-analyses provide further support to current hypertension treatment guidelines by showing that BP lowering can significantly reduce major cardiovascular outcomes largely independent of the agents used, significant risk reduction is found at all hypertension grades (stages), and when systolic BP is lowered below a cut off of 140 mm Hg with some further reduction limited to stroke at systolic BP values just <130 mm Hg. Absolute risk reduction progressively increases higher is total cardiovascular risk, but this greater benefit is associated with a progressively higher residual risk, ie, higher treatment failures.